Evaluating the efficacy and safety of iontophoresis-assisted corneal cross-linking compared to standard CXL in the treatment of keratoconus - Noor Alqudah; Asem Alqudah; Sarah Alshamarti; Zaki Shannak (Indian Journal of Ophthalmology, 2025)
Purpose: To compare the outcomes of standard corneal cross-linking (S-CXL) and iontophoresis-assisted CXL (I-CXL) in Jordanian keratoconus patients over a 12-month follow-up period. Design: This retrospective, observational cohort study included 107 keratoconus patients who underwent either S-CXL (n = 53) or I-CXL (n = 54) between January 2015 and December 2019. Methods: Data collected included demographic information, clinical history, and ophthalmic examinations. The primary outcome was the change in best-corrected visual acuity (BCVA) from baseline to 12 months post-procedure. Secondary outcomes included changes in spherical equivalent, cylindrical values, corneal curvature (K1, K2, Kmean, Kmax), and thinnest corneal location. Postoperative complications, such as corneal haze, keratitis, and the need for penetrating keratoplasty, were also assessed. Statistical analysis was performed using R statistical software. Results: The mean age of patients was 25.0 years, with a male predominance (60%). Decreased vision was the most common symptom (63%). BCVA improvement was similar in both groups at all intervals. At 12 months, the mean BCVA change was 0.05 in the S-CXL group and 0.04 in the I-CXL group. No significant differences were observed in spherical equivalent values. Corneal curvature values (K1, K2, Kmean, Kmax) were significantly higher in the I-CXL group. Postoperative complications were minimal, with 40% of S-CXL patients and 93% of I-CXL patients experiencing no complications. Mild haze was more common in the S-CXL group (54%). Conclusions: S-CXL demonstrated superiority in improving corneal curvature at 6 and 12 months. Postoperative complications were minimal, with higher incidence of mild haze in the S-CXL group. Further studies with larger sample sizes and longer follow-up periods are needed to confirm these results.